Pengaruh Variasi Arus Listrik dan Jumlah Garam Terhadap Efisiensi Generator HHO dalam Proses Elektrolisis - Al Barr, Muhammad Haafizh; Ismail, Nova Risdiyanto; Suwandono, Purbo (PROTON, 2023)
Energy is an important component for human survival and is highly dependent on the availability of energy. given the limited energy from mining materials available today is running low. In terms of production, global environmental issues and the depletion of fossil fuel reserves encourage various R&D on hydrogen production with water as raw material. In order to overcome the above, one solution is to take advantage of the existence of alternative forms of energy by utilizing electrical energy in the form of hydrogen gas stored in H2 which also comes from water (H2O) which can now be used for energy through the Water Electrolysis process where the best H2 gas production efficiency produced is 23.20% with a current variation of 10 A.